FREQUENCY OF ANTITOXOPLASMA ANTIBODIES IN PATIENTS WITH OCULAR PATHOLOGY - Ally, Sirajuddin Hassan; Idris, Muhammad (Journal of Ayub Medical College Abbottabad, 2004)
Background: Toxoplasmosis is a worldwide disease caused by toxoplasma gondii. This disease is prevalent in many parts of the world including Pakistan. Besides other conditions,ocular diseases are also caused by it. Immune response is mounted against this protozoon in the form of antibodies which are detectable in patient’s serum. The present study estimated the seroprevalence of antitoxoplasma antibodies in patients with ocular diseases. Methods: One hundred patients of either sex and age were studied at the ophthalmology units of Jinnah Postgraduate Medical Centre and Lyari General Hospital Karachi. Antitoxoplasma antibodies, both immunoglobulin G and M (IgG & IgM) were detected in the sera of these patients by the recommended methods. Results: Seroprevalence of antitoxoplasma antibodies was highest (60%) in age groups 21 to 40 years. It was seen in either sex but was found to be more common in females. Conclusions: Further studies with improved diagnostic techniques on larger samples are needed to diagnose and treat toxoplasmosis in acute stage in order to minimize the deleterious effects it has on different tissues and organs of the body. Keywords: Antitoxoplasma, Antibodies, Ocular